2017
DOI: 10.1186/s12888-017-1249-7
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of depression and its associated factors among primary caregivers of patients with severe mental illness in southwest, Ethiopia

Abstract: BackgroundDepression is a serious mental illness that affects patients’ treatment outcome and caregiver’s day to day life. The prevalence of depression among caregivers of patients with severe mental illness is greater than the general population. Little is known about depression among primary caregivers of patients with severe mental illness in Ethiopia. This study is aimed at assessing prevalence of depression and associated factors among primary caregivers of patients with mental illness.MethodsA cross-sect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
51
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(57 citation statements)
references
References 19 publications
1
51
5
Order By: Relevance
“…The study was conducted from April 15-June 15, 2018, at Jimma University Medical Center (JUMC) which is one of the oldest governmental hospitals, established in 1937 during the Italian occupation for the service of their soldiers. The psychiatric clinic of JUMC was established in 1988 and gives clinical service for about 15 million population with a total of 40 beds for inpatient service and seven Out Patient Department (OPD) in Southwest Ethiopia [18]. Currently, there are more than 1000 patients with schizophrenia who are attending follow up service at OPD monthly and on average, about 50 patients are visiting psychiatric clinics daily.…”
Section: Study Settingmentioning
confidence: 99%
“…The study was conducted from April 15-June 15, 2018, at Jimma University Medical Center (JUMC) which is one of the oldest governmental hospitals, established in 1937 during the Italian occupation for the service of their soldiers. The psychiatric clinic of JUMC was established in 1988 and gives clinical service for about 15 million population with a total of 40 beds for inpatient service and seven Out Patient Department (OPD) in Southwest Ethiopia [18]. Currently, there are more than 1000 patients with schizophrenia who are attending follow up service at OPD monthly and on average, about 50 patients are visiting psychiatric clinics daily.…”
Section: Study Settingmentioning
confidence: 99%
“…We conducted this study from April 15-June 15, 2018, among people with schizophrenia and attending, follow up service at Jimma University Medical Center (JUMC), psychiatry clinic, Southwest Ethiopia. Jimma University Medical Center is one of the oldest governmental hospitals, established in 1937 during the Italian occupation for the service of their soldiers [23]. The psychiatric clinic of JUMC was established in 1988 and gives clinical service for about 15 million population with a total of 40 beds for in-patient service and seven rooms for Out Patient Department (OPD) in Southwest Ethiopia during the study time [23].…”
Section: Study Settingmentioning
confidence: 99%
“…Jimma University Medical Center is one of the oldest governmental hospitals, established in 1937 during the Italian occupation for the service of their soldiers [23]. The psychiatric clinic of JUMC was established in 1988 and gives clinical service for about 15 million population with a total of 40 beds for in-patient service and seven rooms for Out Patient Department (OPD) in Southwest Ethiopia during the study time [23]. Currently, there are more than 1000 people with schizophrenia who are attending follow up treatments at OPD monthly and on average, about 50 individuals with different mental illnesses are visiting psychiatric clinics daily.…”
Section: Study Settingmentioning
confidence: 99%
“…In most studies, female caregivers were shown to have higher burden 2,19 of caregiving and increased risk of depression. In contradiction, this study showed that male caregivers screened positive for depression.…”
Section: Discussionmentioning
confidence: 99%